2020
DOI: 10.17097/ataunizfd.596530
|View full text |Cite
|
Sign up to set email alerts
|

Tuz Stresinin Nohut (Cicer arietinum L.) ve Bezelyede (Pisum sativum L.) Tohum Çimlenmesi Üzerine Etkileri

Abstract: Bu makaleye atıfta bulunmak için / To cite this article: Dadaşoğlu, E., Ekinci, M., Yıldırım, E., 2020. Effects of Salt Stress on Seed Germination of Chickpea (Cicer arietinum L.) and Pea (Pisum sativum L.). Atatürk Univ. J. of Agricultural Faculty, 51 (1): 53-62.ABSTRACT: Salinity is one of the most severe environmental factors limiting the productivity of agricultural crops. This study was conducted to determine the effect of salt stress on seed germination in chickpea (Cicer arietinum L.) and pea (Pisum sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In the 1.0 Put application, in which putrescine was used alone without salt stress, higher results in terms of germination properties were obtained compared with the control (Table 2). Similar to the results obtained in this study, negative effects of salt stress on germination have been reported in previous studies on different vegetables (Dadaşoğlu and Ekinci, 2013;Koç et al, 2014;Mena et al, 2015;Mohamedsrajaden, 2019;Kibar et al, 2020). It was determined that putrescine application alone without salt stress increased the germination rate, radicle and plumule length in pepper compared to the control, and putrescine was more effective especially at low concentrations (Khan et al, 2012).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the 1.0 Put application, in which putrescine was used alone without salt stress, higher results in terms of germination properties were obtained compared with the control (Table 2). Similar to the results obtained in this study, negative effects of salt stress on germination have been reported in previous studies on different vegetables (Dadaşoğlu and Ekinci, 2013;Koç et al, 2014;Mena et al, 2015;Mohamedsrajaden, 2019;Kibar et al, 2020). It was determined that putrescine application alone without salt stress increased the germination rate, radicle and plumule length in pepper compared to the control, and putrescine was more effective especially at low concentrations (Khan et al, 2012).…”
Section: Resultssupporting
confidence: 91%
“…In the study, it was also stated that 1 mM salicylic acid application inhibited germination (Ulukapı et al, 2020). In studies conducted on different vegetables, it was found that as salinity increased, the germination rate decreased, and salicylic acid applications under salt stress increased the germination rate (Entesari et al, 2012;Dadaşoğlu and Ekinci, 2013;Akbıyık, 2019).…”
Section: Resultsmentioning
confidence: 98%
“…In the studies conducted with Marrubium vulgare L. and Mentha pulegium L., which are also members of the same family, it was concluded that the increase in salinity decreased the germination percentage (Nedjimi et al, 2020;Azad et al, 2021). In other studies on salinity (Akram et al, 2020;Dadaşoğlu et al, 2020;Dehnavi et al, 2020;Mondal et al, 2020;Singh et al, 2020;Zhumabekova et al, 2020;Bahrabadi et al, 2021;De Rossi et al, 2021;El Hamdaoui et al, 2021;Shariatinia et al, 2021;Tonguç et al, 2021;Zeng et al, 2021), it has been reported that increasing the salt concentration decreases the germination percentage.…”
Section: Discussionmentioning
confidence: 94%